Pengembangan Model Pembelajaran Pendidikan Jasmani Berbasis Game-Based Learning Terintegrasi Augmented Reality untuk Meningkatkan Keterampilan Motorik Siswa - Novia Rozalini; Twk Moh Iqbal; Dhanil Fitri Ama; Nugraha Pratama (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to develop and evaluate the effectiveness of a game-based Physical Education (PE) learning model integrated with Augmented Reality (AR) to enhance elementary school students’ motor skills. Employing a Research & Development (R&D) approach with the ADDIE framework (Analysis, Design, Development, Implementation, and Evaluation), the research involved expert validation, limited trials, and field testing. The results demonstrate that the AR-integrated game-based PE learning model is feasible, as confirmed by material and media experts with a “Good” rating. Trial findings show significant improvements in students’ fundamental motor skills, particularly coordination, balance, agility, and accuracy. Moreover, the integration of AR in interactive games increased students’ motivation, engagement, and enthusiasm in PE classes. In conclusion, the AR-integrated game-based learning model is effective in enhancing motor skills while creating an engaging and interactive learning environment, making it highly relevant to the needs of elementary school students in the digital era. Keywords: Physical Education, Learning Model, Game-Based Learning, Augmented Reality, Motor Skills, Basic Motor Skills.